2017
DOI: 10.1097/shk.0000000000000740
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia Induces Inflammation and Cytotoxicity in Human Adult Cardiac Myocytes

Abstract: Supplemental oxygen (O2) is used as adjunct therapy in anesthesia, emergency, and intensive care medicine. We hypothesized that excessive O2 levels (hyperoxia) can directly injure human adult cardiac myocytes (HACMs). HACMs obtained from the explanted hearts of transplantation patients were exposed to constant hyperoxia (95% O2), intermittent hyperoxia (alternating 10 min exposures to 5% and 95% O2), constant normoxia (21% O2), or constant mild hypoxia (5% O2) using a bioreactor. Changes in cell morphology, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…18 In humans it has been shown that compared to their normoxic counterparts, cardiomyocytes exposed to constant hypoxia have elevated secretion levels of inflammatory cytokines, including IL-1, IL-6, IL-8, as well as certain growth factors and chemokines. 15 The initial cause of myocardial damage in feline HCM that would trigger the observed remodeling processes is still unknown, but hypoxia appears likely considering the present findings. 4,12 So far unknown structural or functional myocardial alterations could result in latent myocardial hypoxia, leading to individual cardiomyocyte degeneration and death.…”
Section: Involvement Of Inflammatory Cytokines In Myocardial Remodelimentioning
confidence: 67%
“…18 In humans it has been shown that compared to their normoxic counterparts, cardiomyocytes exposed to constant hypoxia have elevated secretion levels of inflammatory cytokines, including IL-1, IL-6, IL-8, as well as certain growth factors and chemokines. 15 The initial cause of myocardial damage in feline HCM that would trigger the observed remodeling processes is still unknown, but hypoxia appears likely considering the present findings. 4,12 So far unknown structural or functional myocardial alterations could result in latent myocardial hypoxia, leading to individual cardiomyocyte degeneration and death.…”
Section: Involvement Of Inflammatory Cytokines In Myocardial Remodelimentioning
confidence: 67%
“…indicated that alternating hypoxia/hyperoxia may induce a more reliable pro-angiogenic regulators up-regulation compared with normoxia 11 . Furthermore, several studies have been reported that high oxygen concentrations can modulate mRNA expression of several genes and related protein secretion including hypoxia inducible factor (HIF)-1α (a master oxygen sensitive transcriptional regulator), vascular endothelial growth factor-A (VEGFA), and interleukin (IL)-8 15 , 19 - 21 . Particularly VEGFA, VEGF receptor-1 (VEGFR1/Flt-1) and VEGFR2 (KDR/Flk-1) are the critical pro-angiogenic factor for vascular formation 11 , 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Several other factors contribute to the complex response of the cell to hyperoxia, i.e., STAT (signal transducers and activators of transcription protein)-subtypes, CEBP (ccat/enhancer binding protein), c-myc, Fra-1, junB and c-Fos. To better understand the tissues’ responses to hyperoxia, several recent studies investigated proteomic alterations in response to various degrees of hyperoxia ( Konsavage et al, 2013 ; Hinkelbein et al, 2015 ; Hafner et al, 2017b ). The complexity of the cellular proteome as well as the use of different experimental and analytical protocols necessarily leads to different results and conclusions in these studies.…”
Section: Molecular Biology Of Oxygen Sensing In Normoxia Hypoxia Andmentioning
confidence: 99%